دور الدول المغاربية في مواجهة التهديدات الأمنية اللاتماثلية (الجزائر نموذجاً) - يـجـار عــبـيـر; رقولي كريم (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
يعاني العالم من تهديدات لم تُعهد في السابق وهو ما أطلق عليها بالتهديدات اللاتماثلية والتي يكون فيها الطرفين غير متكافئين، وهذا النوع من التهديدات مس الدول المغاربية فأصبحت هاجس أمني لديها لا بد من درئه والحد من تداعياته، ومن بين تلك التهديدات ظاهرة الجريمة المنظمة، الجماعات الإرهابية، تجارة الأسلحة، الهجرة الغير شرعية، ومن ثم فقد عملت الجزائر كدولة من دول المغرب العربي على الحد من آثار تلك التهديدات على الأمن المغاربي وفق استراتيجيات وآليات مبنية على عقيدة أمنية راسخة لدى الدولة الجزائرية، ولعل أهم تلك الاستراتيجيات حول الظاهرة الإرهابية مثلاً هو العمل على تجفيف منابع الأموال التي تقتات منها الجماعات الإرهابية، وتجريم استخدام تكنولوجيا المعلومات لأغراض تجنيد الإرهاب مع مناداتها الدائمة بضرورة تنسيق استخباراتي فعال بين دول المنطقة. The world suffers from threats that have not been pledged in the past, which has been called asymmetric threats in which both sides are unequal, and this kind of threat has affected the Maghreb countries, which has become a security concern that must be addressed and reduced its repercussions including the phenomenon of organized crime, terrorist groups arms trade, illegal immigration, and thus Algeria as a Member of the Maghreb has worked to reduce the effects of those threats on Maghreb security according to strategies based on a well-established security doctrine. The Algerian state, perhaps the most important of these strategies on the terrorist phenomenon, for example, is to work to dry up the sources of funds from which terrorist groups are derived, and to criminalize the use of information technology for the purposes of recruiting terrorism, while constantly calling for effective intelligence coordination among the countries of the region.